Feeding Pattern of Children Under 2 Years of Age with Severe Malnutrition Presenting in Hayatabad Medical Complex - Taj, Furqan; Khan Afridi, Jahanzeb; Fazal, Ammad; Hussain, Muhammad Kashif; Khan Afridi, Muhammad Jabir; Khan, Farhan Zeb (Indus Journal of Bioscience Research, 2025)
Background: To determine the frequency and distribution of various feeding patterns among children under two years of age diagnosed with severe malnutrition presenting at Hayatabad Medical Complex, Peshawar. Methods: A cross-sectional study was conducted over a period of six months (16 September, 2024 to 15 March, 2025) in the Department of Pediatrics, MTI-Hayatabad Medical Complex, Peshawar, Pakistan. A total of 118 malnourished children aged 2 to 12 months were enrolled using non-probability consecutive sampling. Data on age, gender, vaccination status, residence, and feeding practices were collected through caregiver interviews and clinical assessments. Feeding patterns were categorized as exclusive breastfeeding, predominant breastfeeding, formula feeding, or fresh cow’s milk feeding. Data were analyzed using SPSS version 22.0. Chi-square tests were applied to assess associations, with p ≤ 0.05 considered significant. Results: Exclusive breastfeeding was reported in 32.2% of participants, while 28.0% received formula, and 22.0% were fed fresh cow’s milk. Age group, vaccination status, and duration of malnutrition were significantly associated with feeding practices. Younger infants, vaccinated children, and those with shorter durations of malnutrition were more likely to be exclusively breastfed. Conclusion: The study highlights low rates of exclusive breastfeeding among malnourished infants and emphasizes the need for improved maternal education and support programs to encourage optimal feeding practices. Integration of nutritional counseling into routine immunization and child health services may offer a practical strategy for reducing malnutrition.